Market-oriented reforms and "high stakes" testing: Incentives and consequences - Anne West; Hazel Pennell (Les éditions de la Maison des sciences de l'Homme, 2005)
This paper focuses on the use of "high stakes" tests and examinations, which by definition have serious consequences; high stakes tests are used in an attempt to raise standards and to evaluate school systems. A range of dysfunctional consequences of high stakes testing are observed, including teaching to the test and a narrowing of the curriculum. Moreover, we cannot be confident that the improvements observed in high stakes tests reflect authentic improvements in achievement. Finally, the emphasis on test and examinations results appears to have focused attention on internal school processes as the key means of improving learning and knowledge, rather than addressing structural issues to do with pupil mix or structural inequalities within society. It is concluded that the incentives are such that the continued use of high stakes tests does not enable pupils' genuine learning to be measured.